Kajian Kritis Al-Dakhil Dari Jalur Tafsir Bathiniyah - Rolan Nasution; Zubaidah Nasution; Mina Sari Siregar; Hary Sahputra (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study examines the challenge of ad-dakhil (foreign elements) in Qur’anic interpretation, particularly through the Baṭhiniyah interpretive approach, which prioritizes inner meanings while neglecting the apparent (ẓāhir) meaning and established exegetical methodologies. Such interpretations are considered to have the potential to distort Qur’anic meanings and undermine the normative foundations of Islamic law. The study aims to critically analyze the concept of ad-dakhil within Baṭhiniyah exegesis and identify its methodological deviations, as well as scholarly perspectives on its legitimacy in Qur’anic studies. Employing library research with a qualitative-descriptive and analytical-critical approach, data were collected from classical and contemporary tafsir works, Islamic legal scholarship, and relevant books and journal articles. The analysis focuses on epistemological foundations, interpretive methods, and theological and normative implications. The findings reveal that Baṭhiniyah exegesis constitutes a major channel for the infiltration of ad-dakhil due to its disregard for linguistic rules, contextual considerations of revelation, and reliance on exclusive, unverifiable inner authority claims. Consequently, most exegetical scholars regard this approach as a methodological deviation that threatens a comprehensive understanding of Islamic teachings. The study recommends strengthening literacy in valid exegetical methodologies and encourages further research on other channels of ad-dakhil, including ideological, political, and philosophical influences, to preserve the integrity of Qur’anic interpretation.